2018
DOI: 10.9758/cpn.2018.16.2.209
|View full text |Cite
|
Sign up to set email alerts
|

Unipolar Mania: A Particular Aspect of Bipolar Disorder in Tunisia

Abstract: ObjectiveUnipolar mania is a clinical reality in our daily practice. Many authors suggested that bipolar patients can have only manic episodes without depressions. These findings lead us to explore more this particularity.MethodsWe conduct a retrospective, descriptive and comparative study including 173 patients, followed for bipolar disorder type I, according to the Diagnostic and Statistical Manual of Mental Disorders fifth edition criteria, during the period between January 2008 and December 2015. Two group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 24 publications
4
6
2
Order By: Relevance
“…This difference was even more pronounced in the two adolescent studies (5.6% vs 22.0%). This is in agreement with a long‐term follow‐up study of a sample of hospital admissions in Zurich, with the study of Grobler et al, with the reviews of Yazici and Mehta as well as with the recent finding of Amamou et al in Tunisia . Our observation of a lower proportion of bulimia/binge eating disorders among adults with unipolar mania than among those with BP‐I disorder is a new finding.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This difference was even more pronounced in the two adolescent studies (5.6% vs 22.0%). This is in agreement with a long‐term follow‐up study of a sample of hospital admissions in Zurich, with the study of Grobler et al, with the reviews of Yazici and Mehta as well as with the recent finding of Amamou et al in Tunisia . Our observation of a lower proportion of bulimia/binge eating disorders among adults with unipolar mania than among those with BP‐I disorder is a new finding.…”
Section: Discussionsupporting
confidence: 93%
“…In this connection, Douki et al found unipolar mania to be three times more common among patients in Tunisia than in France. These high rates in Tunisia were recently confirmed by Amamou et al Both Douki et al and Amamou et al attributed these differences to cultural variations and seasonality. Cultural differences in the awareness and experience of depressive and manic symptoms represent a significant limitation of studies on affective disorders.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…9 A Indian study published by Avasthi et al reported that 11 out of 50 patients with recurrent manic episodes met the criteria for seasonal affective disorder and had onset in summer or winter rather than autumn or spring. 25 24 However, our study did not find any statistically significant difference though marginally higher in the BPAD group.…”
Section: Discussioncontrasting
confidence: 62%
“…In a study from Tunisia, Amamou et al reported that the rapid cycling phenomena were comparable between the two groups. 24 Psychotic symptoms in the first episode, suicidality, comorbid anxiety, substance use and medical illness, were more common among the BPAD group. In contrast, the seasonality was more common among UM group in our study.…”
Section: Discussionmentioning
confidence: 95%